Review on Buckling and Bending Analysis of Functionally Graded Beam with and without Crack - Neamah, Raghad Azeez; Nassar, Ameen Ahmed; Alansari, Luay S. (Basrah Journal for Engineering Sciences, 2022)
The functionally graded beam is a wide field of research, which attracts great interest today in the field of engineering, science, and medicine society. This type of beam is made from functionally graded material that is characterized by several properties one of them is the high strength to weight ratio. In the current years, this beam has witnessed great developments in the mechanism of its composition and the materials used in its manufacture. This research provides an overview of the properties, types, advantages and challenges, and applications of the functionally graded materials. In addition, this paper review provides a summary of the analysis of bending and buckling that occurs on the functionally graded beam with and without crack effect from (2008-2021) year. Through this review, the following was noted: Firstly, a small number of researchers have worked experimentally, and the properties of a beam in most of the research are gradual towards thickness using the mixing rule. Secondly, the crack has a very severe effect on the behavior of both bending and buckling for the graded beam. This critical review can be considered a milestone in future analyzes of the graded beam and is also beneficial to designers and researchers working in this field.